Preparation and characterisation of new oxide ion conductors in the Bi2-(W, Mo)-6 system - Sim, Leng Tze (2000)
Bh W06, BhMo06 and their related materials were prepared by solid state reactions. The phase purity of the materials was determined by X-ray diffraction (XRD). Further characterisation using Fourier-transform infrared (FT-IR) spectroscopy, differential thermal analysis (DTA) and impedance spectroscopy were carried out on single phase materials. Thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) were also performed on selected samples. Only Nb and Ta could be introduced as dopant into Bh W06 with rather limited solid solution formation while introduction of dopants other than W into y-BbMo06 was unsuccessful. From results obtained in IR and DT A studies, it appears that the metal-oxygen bondings in Nb- and Ta-doped materials are weaker as compared to those in the parent material, Bi2W06. The conductivity of these materials was about two orders of magnitude higher than that of Bi2 W06. Introduction of lower valency cation results in the creation of oxygen vacancies resulting in higher conductivity. The IR and XRD patterns of both y-Bh W06 and y-BhMo06 are very similar since the materials are isostructural. Complete solid solutions in the y-Bh W06 - y-BhMo06 system were obtained when prepared via low temperature route. This was made possible since the HumeRothery rules were fully obeyed by these materials. However, some of these materials were metastable and decomposed into mixed phases upon heating at higher temperatures. Generally, the conductivity in the system was comparable. The conductivity of y' -BhMo06 is very dependent on sintering temperature and time. It is possible that loss of oxygen occurs upon sintering at elevated temperatures leading to the formation of non-stoichiometric y' -BhMo06-S. From ac impedance studies, oxide ions appear to be the main charge carriers in this material. Phase diagram in the Bh W06 - Bi2Mo06 system was constructed based on results obtained from different heating experiments, XRD and DTA results.